THE EFFECTIVENESS OF TEAMS GAMES TOURNAMENT STRATEGY TO TEACH READING COMPREHENSION IN DESCRIPTIVE TEXT TO THE TENTH-GRADE STUDENTS OF SMK PEMUDA KUTOREJO - Fahrur Ardiyanto; Fahrur Rijal Ardiyanto (Channing : Journal of English Language Education and Literature, 2022)
Students could enrich their knowledge by reading books or from the other sources, whether in academic or non academic purposes. Reading activity helped to improve the students’ learning in class, especially in English learning. Moreover, besides writing, speaking, and listening, reading had become one of the essential skills. In improving the reading skill, students also had to improve their comprehension through reading some texts. This research was aimed to measure the effectiveness of using Teams Games Tournament strategy to teach reading comprehension in descriptive text to the tenth-grade students of SMK PEMUDA Kutorejo. The method which had applied in this research was quasi-experimental research. There were two classes, experimental and control classes which had been given the post-test. The average score in control class was 62,90 and experiment class was 76,83. After collecting the data, the researcher had to calculate and analyze them by using t-test formula. The result showed the t-value was 7,97, which is greater than t-table 1,67 at 0,05 levels of significance for df is 60. As a conclusion, Teams Games Tournament strategy was effective when it is implemented in reading comprehension through descriptive text in tenth-grade class. It could be an alternative way to teach reading descriptive text for the better strategy which has given by those teacher to find out the students comprehension in their reading skill.